Quantum confinement-induced semimetal-to-semiconductor evolution in large-area ultra-thin PtSe2 films grown at 400 °C - Duesberg, Georg (My University, 2019)
In this work, we present a comprehensive theoretical and experimental study of quantum confinement in layered platinum diselenide (PtSe2) films as a function offilm thickness. Our electrical measurements, in combination with density functional theorycalculations, show distinct layer-dependent semimetal-to-semiconductor evolution in PtSe2films, and highlight the importance ofincluding van der Waals interactions, Green’s function calibration, and screened Coulomb interactions in the determination of thethickness-dependent PtSe2energy gap. Large-area PtSe2films of varying thickness (2.5–6.5 nm) were formed at 400 °C by thermallyassisted conversion of ultra-thin platinumfilms on Si/SiO2substrates. The PtSe2films exhibitp-type semiconducting behavior withhole mobility values up to 13 cm2/V·s. Metal-oxide-semiconductorfield-effect transistors have been fabricated using the grownPtSe2films and a gatefield-controlled switching performance with anION/IOFFratio of >230 has been measured at roomtemperature for a 2.5–3 nm PtSe2film, while the ratio drops to <2 for 5–6.5 nm-thick PtSe2films, consistent with a semiconducting-to-semimetallic transition with increasing PtSe2film thickness. These experimental observations indicate that the low-temperaturegrowth of semimetallic or semiconducting PtSe2could be integrated into the back-end-of-line of a silicon complementary metal-oxide-semiconductor process.
Keywords: semiconducting-to-semimetallic transition; quantum confinement; layered platinum diselenide (PtSe2; semiconducting-to-semimetallic transition; quantum confinement; layered platinum diselenide (PtSe2